Indigenous peoples confront modern conservation in Costa Rica (1970-2020). An approach from the critical sociology of power - Vargas Mena, Emilio (2025)
This article highlights relevant findings and insights of a pedagogical and investigative experience in the Wildlife Conservation and Management Graduate Program of the National University of Costa Rica. Through its publication as a book, the research experience contributes, from the critical Sociology of power, to the contemporary environmental and political histories of the indigenous peoples and territories in Costa Rica. It synthesizes, with an academic dissemination purpose, some fundamental outcomes found and discussed in the three major parts of the research report: a) the political and environmental historical context, b) the protected areas and the Bribri/Cabecar peoples in Ditsö-ké (Talamanca Range), and c) the cooperation and conflict relationships between modern conservation and the  Brunka, Maleku and Chorotega peoples. Several documents with primary and secondary information from different types of archives were compiled and analyzed, including published texts by the indigenous movement.